An experimental investigation into mechanical and thermal properties of hybrid woven rattan/glass-fiber-reinforced epoxy composites - Irawan, Agustinus Purna; Anggarina, Paula Tjatoerwidya; Utama, Didi Widya; Najid, Najid; Mohd Zulkifly, Abdullah; Siregar, Januar Parlaungan; Cionita, Tezara; Fitriyana, Deni Fajar; Jamiluddin, Jaafar; Hadi, Agung Efriyo; Rihayat, Teuku (MDPI, 2022)
The investigation of hybrid, woven, natural fiber-reinforced polymer composites as a substitute reinforcement for fiber polymer composites has recently caught the interest of academics, industry, and researchers. Woven, natural fiber composites have been implemented in many different applications, including parts for automobiles, household items, flooring, aerospace, and ballistic materials. Therefore, this research seeks to establish the thermal and mechanical characteristics of composites made from rattan strips (RS) and glass fiber (GF)-reinforced epoxy resin (ER). Other than that, the impact of layering configurations with respect to the thermal and mechanical characteristics of the RS and GF will be determined. Hand lay-up and a hydraulic press machine produce hybrid, woven RS and GF laminates. The hybrid composite’s mechanical properties will be investigated using impact, tensile, and flexural tests. The hybrid woven of the GF/RS/RS/RS/GF composite sequence demonstrated the highest mechanical properties in comparison to other sequences. The increase from one to three layers of RS in the core layer of GF hybrid composites enhanced the flexural, impact, and tensile properties. In addition, the hybridization of rattan and GF is more thermally stable, as recorded by the high decomposition temperature. As a finding of the research, the woven RS and GF hybrid is a potential material for automotive applications such as car bumpers, for example.